Ambient Odor Exposure Affects Food Intake and Sensory Specific Appetite in Obese Women - Proserpio, Cristina; Invitti, Cecilia; Boesveldt, Sanne; Pasqualinotto, Lucia; Laureati, Monica; Cattaneo, Camilla; Pagliarini, Ella (Frontiers in Psychology, 2019)
Food odors are important in food perception not only during consumption, but also in anticipation of food. Even though it is well established that smell is involved in eating behavior, its role in affecting actual food consumption is still unclear, especially in morbidly obese subjects, who are reported to be more affected by sensory cues than lean subjects. The aim of the present study was to investigate the influence of ambient odor exposure on ad libitum food intake and on sensory specific appetite in obese women. Thirty obese women (BMI: 34.9 ± 0.8 kg m-2; age: 50.8 ± 1.8) attended two sessions in which they were exposed to a bread odor dispersed, in a detectable but mild concentration, in the test room (“scented” condition) and to a control condition (“unscented” condition). Participants filled out a questionnaire on general appetite before entering the test room and completed a sensory specific appetite questionnaire (including 12 specific products) about 10 minutes after entering the test room. After approximately 15 minutes of exposure, the ad libitum intake of a low energy dense food product (vegetable soup) was measured. The “scented” condition significantly (p<0.01) increased the amount of soup eaten compared to the “unscented” condition (466.4 ± 33.1g; 368.9 ± 33.2g, respectively). Moreover, the odor exposure induced sensory specific appetite for congruent food products in term of taste and energy density, as well as a significant increase in general appetite scores (p<0.001). In conclusion, ambient odor exposure to a food odor affected the intake of a low energy food in obese women and stimulated appetite for congruent products. This could have important implications for influencing energy intake of individuals.